Perceived Information Quality of an AI-Powered Chatbot: The Case of Sabrina at Bank BRI - Onny Amelya; Aminudin Azis; Niza Nurmalasari (International Journal of Entrepreneurship and Tourism, 2025)
The use of Artificial Intelligence (AI)-based chatbot technology has transformed customer service by enabling efficient and interactive digital communication. Chatbot Sabrina, a virtual assistant developed by PT Bank Rakyat Indonesia (Persero) Tbk, is designed to provide banking information and support customer needs. This study explores customer perceptions in Madiun City regarding the information quality delivered by Chatbot Sabrina. Utilizing a quantitative descriptive method, the study applied purposive sampling involving 40 respondents who are active BRI customers and users of Sabrina. Data were analyzed using descriptive statistics, referencing the Information Quality framework by DeLone and McLean, which includes four key dimensions: accuracy, relevance, completeness, and ease of understanding. Results show that most respondents perceive the chatbot’s information quality positively. Specifically, 58% agreed that the information is accurate and unambiguous, 70% found it relevant to their needs, 58% believed it offers complete and structured information, and 65% confirmed that the information is easy to understand. These findings suggest that Chatbot Sabrina effectively meets customer information needs and enhances service experience through reliable and user-friendly digital interactions.